Bilateral Optic Nerve Atrophy Case Report - Naqeeb, Mohammed R.; Abdulmannan, Dina M (Majalah Kedokteran Bandung, 2024)
Wolfram syndrome, also known as DIDMOAD or juvenile onset diabetes mellitus, optic nerve atrophy, diabetes insipidus, and deafness, is a genetic neurological condition. This case report provides a description on the first instance of Wolfram syndrome in a Saudi family, which manifested as proliferative diabetic retinopathy and a powder-like cataract, among the other unusual ophthalmological findings. This case involved a 27-year-old Saudi woman with bilateral optic nerve atrophy who was first diagnosed with diabetes mellitus at the age of 8 years. At the age of 18, bilateral optic nerve atrophy was identified. At the age of 27, diabetes insipidus and hearing loss were verified. There were no signs of renal, neurological, or psychiatric issues. Atypical ophthalmological traits were examined and addressed in this study. Any individual with bilateral optic nerve atrophy and insulin-dependent diabetes mellitus within the first 30 years of life should be evaluated for the possibility of Wolfram syndrome. Microvascular diabetes is an incredibly rare complication of Wolfram syndrome. Early diagnosis, treatment, and prevention of severe consequences can result in improved survival rates and quality of life.